A day in the life of your body : find out what's going on under your skin - Kay, Liz; Grimes, Amy; Jallow, Binta; Richards, Vicky; Limerick, Anna (Dorling Kindersley Limited, 2025)
Ever wondered what happens inside your body from the moment you wake up until you fall asleep? Follow A Day in the Life of Your Body, uncovering the amazing secrets of the human body along the way. From the adrenaline rush of a morning run to the brainpower behind solving math problems, this book dives into the fascinating world of all the organs and systems that keep us going. Why do we get goosebumps? What causes us to itch? Discover the answers to these questions and more with fun facts, colorful illustrations, and engaging explanations. Perfect for curious minds ages 9-12, this book transforms everyday activities into a thrilling scientific adventure. Get ready to be amazed by the extraordinary things your body does every single day!